Mechanism of Action of Bortezomib and the New Proteasome Inhibitors on Myeloma Cells and the Bone Microenvironment: Impact on Myeloma-Induced Alterations of Bone Remodeling. (22nd October 2015) - Accardi, Fabrizio; Toscani, Denise; Bolzoni, Marina; Dalla Palma, Benedetta; Aversa, Franco; Giuliani, Nicola
Abstract : Multiple myeloma (MM) is characterized by a high capacity to induce alterations in the bone remodeling process. The increase in osteoclastogenesis and the suppression of osteoblast formation are both involved in the pathophysiology of the bone lesions in MM. The proteasome inhibitor (PI) bortezomib is the first drug designed and approved for the treatment of MM patients by targeting the proteasome. However, recently novel PIs have been developed to overcome bortezomib resistance. Interestingly, several preclinical data indicate that the proteasome complex is involved in both osteoclast and osteoblast formation. It is also evident that bortezomib either inhibits osteoclast differentiation induced by the receptor activator of nuclear factor kappa B (NF- κ B) ligand (RANKL) or stimulates the osteoblast differentiation. Similarly, the new PIs including carfilzomib and ixazomib can inhibit bone resorption and stimulate the osteoblast differentiation. In a clinical setting, PIs restore the abnormal bone remodeling by normalizing the levels of bone turnover markers. In addition, a bone anabolic effect was described in responding MM patients treated with PIs, as demonstrated by the increase in the osteoblast number. This review summarizes the preclinical and clinical evidence on the effects of bortezomib and other new PIs on myeloma bone disease.